Effect of umbilical cord blood stem cell transplantation on restenosis after endovascular interventional therapy for diabetic hindlimb vascular disease. - Hai-Xia Ding (Public Library of Science (PLoS), 2021)
This study aimed to investigate the mechanism of human umbilical cord blood stem cell (HUCBSC) transplantation on restenosis after percutaneous transluminal angioplasty (PTA) for diabetic hindlimb vascular disease in rabbits. After successfully preparing a rabbit model of diabetic hindlimb vascular disease, 16 rabbits were randomly assigned to two groups. Of these, 8 rabbits received PTA surgery alone (PTA group), and the other 8 rabbits received PTA and HUCBSC (PTA+HUCBSC group) treatments. Five more healthy rabbits were set as healthy control (HC group). Samples were collected after 4 weeks of treatment. The expressions of regulator of calcineurin 1 (RCAN1) and calcineurin A (CnA) in the diseased artery were detected by immunofluorescence staining. The distribution of HUCBSCs was observed by pathological examination in transplanted artery, distal artery, and liver. Cytology experiments were applied to assess the levels of JAK and STAT3, and the migration and proliferation of human aortic vascular smooth muscle cells (HA-VSMC). In the rabbit model of diabetic vascular lesions in the hindlimbs, we found the stenosis of the femoral artery became more and more serious with time, and the expression level of PCNA positive cells was also gradually increased. The expression levels of RCAN1 and CnA in the PTA+HUCBSC group were significantly lower than those in PTA group. HUCBSC inhibited the migration and proliferation of HA-VSMC via JAK/STAT3 pathway. After HUCBSC local transplantation, HUCBSC had no distal tissue distribution. HUCBSC transplantation may prevent restenosis after PTA of diabetic hindlimb vascular disease through JAK/STAT3 pathway.